2000
DOI: 10.1159/000030476
|View full text |Cite
|
Sign up to set email alerts
|

Value of Free Prostate-Specific Antigen (Hybritech Tandem-R) in Symptomatic Patients Consulting the Urologist

Abstract: Introduction: Prostate-specific antigen (PSA) is a widely used tumor marker in the detection and follow-up of adenocarcinoma of the prostate. Selection of candidates for prostate biopsies is hampered by the lack of specificity resulting in a large number of unnecessary biopsies. The intention of our study was to compare the percent free PSA (f-PSA; Hybritech Tandem-R) with total PSA and age-specific PSA reference values to evaluate the clinical benefit in detecting patients with prostate cancer (PC) in a selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
1
0
1
Order By: Relevance
“…2 shows the screening accuracy summary of our study and that of 14 other studies reported by Merriel et al [25] with a PSA of 4 ng/mL or higher as a cutoff. The sensitivity in this study was comparable to those of past reports, [11][12][13][14][15][16][17][18][19][20][21][22][23][24] but the speci city was higher. Figure 2 shows the ROC curves for identifying the optimal cutoff for PSA for predicting prostate cancer in each age group.…”
Section: Screening Accuracysupporting
confidence: 89%
“…2 shows the screening accuracy summary of our study and that of 14 other studies reported by Merriel et al [25] with a PSA of 4 ng/mL or higher as a cutoff. The sensitivity in this study was comparable to those of past reports, [11][12][13][14][15][16][17][18][19][20][21][22][23][24] but the speci city was higher. Figure 2 shows the ROC curves for identifying the optimal cutoff for PSA for predicting prostate cancer in each age group.…”
Section: Screening Accuracysupporting
confidence: 89%
“…Sin embargo, y como podemos apreciar en la tabla 1, existe una gran variabilidad en los puntos de corte de PSA para cada grupo de edad. Además, el aumento de la especificidad que proporciona el PSA-edad en los sujetos mayores de 60 años conlleva una pérdida en el diagnóstico de un 20-30% de CaP 35,36 .…”
Section: Rangos De Referencia Específicos De Edadunclassified
“…The principal drawback of the PSA test is its imperfect specificity, owing to the fact that common conditions, such as benign prostate hyperplasia (BPH) and prostatitis, can cause borderline or even markedly abnormal test results [3,4]. These results can lead to expensive diagnostic evaluation and unwarranted patient anxiety.…”
Section: Introductionmentioning
confidence: 99%